Implementation Of Csr By Pt Rajawali Nusantara Indonesia In Supporting 2030 Sdgs Amid And Beyond Covid-19 - Putra Yustono, Dewanta Arya; Djamhuri, Ali (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
Companies today are oriented not only toward generating profits but also toward fulfilling sustainability responsibilities through the implementation of Corporate Social Responsibility (CSR). CSR serves as a means for companies to demonstrate social responsibility and reflects ethical commitments in building long-term performance. Moreover, companies are expected to contribute to the 2030 Sustainable Development Goals (SDGs), which emphasize economic welfare, environmental preservation, and intergenerational social justice. The COVID-19 pandemic, which struck Indonesia in early 2020, posed significant challenges to CSR implementation. This qualitative descriptive study aims to examine the CSR contribution of PT Rajawali Nusantara Indonesia (ID Food) to the achievement of the 2030 SDGs in Indonesia, and to explore the relationship between the COVID-19 pandemic and the company’s CSR performance in reaching those goals. The qualitative approach is employed due to the comprehensive nature of CSR practices, which involve symbolic and expressive dimensions. The findings indicate that the company has supported the 2030 SDGs through CSR programs focused on assisting micro, small, and medium enterprises (MSMEs). During the pandemic, CSR activities continued with adjustments in both distribution mechanisms and the types of assistance provided. Based on these findings, the study concludes that CSR practices that are adaptive, collaborative, and responsive to critical needs are effective in supporting the achievement of the SDGs.